2021
DOI: 10.1093/narcan/zcab030
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-mediated delivery of RNAi-based therapeutics for the treatment of oncological diseases

Abstract: RNA interference (RNAi)-based therapeutics (miRNAs, siRNAs) have great potential for treating various human diseases through their ability to downregulate proteins associated with disease progression. However, the development of RNAi-based therapeutics is limited by lack of safe and specific delivery strategies. A great effort has been made to overcome some of these challenges resulting in development of N-acetylgalactosamine (GalNAc) ligands that are being used for delivery of siRNAs for the treatment of dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 160 publications
(214 reference statements)
0
29
0
Order By: Relevance
“…In the future, we plan to test the efficacy of the iRHOM siRNA treatments in vivo and optimize drug delivery. Several studies have indicated that iron scavenging receptors, such as SCARA5, are upregulated on the surfaces of MAP-infected macrophages ( 39 41 ). Therefore, if we conjugate ferritin to the iRHOM siRNAs, this should effectively deliver the treatment to the cytosol of the effected cells ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the future, we plan to test the efficacy of the iRHOM siRNA treatments in vivo and optimize drug delivery. Several studies have indicated that iron scavenging receptors, such as SCARA5, are upregulated on the surfaces of MAP-infected macrophages ( 39 41 ). Therefore, if we conjugate ferritin to the iRHOM siRNAs, this should effectively deliver the treatment to the cytosol of the effected cells ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Current delivery systems of miR-34a mainly utilize the packaged vehicle strategy [ 14 ]. The other platform is unpackaged or ligand-conjugates, such as folate [ 65 , 66 ]. Despite extensive research in the field, the translation of miR-34a therapeutics into the clinic has been hindered by several issues including delivery vehicle-associated toxicity, inefficient cellular uptake and serum stability, and limited specificity to targeted tumors.…”
Section: Mir-34a Therapeutic Development For Aggressive Pcamentioning
confidence: 99%
“…Despite extensive research in the field, the translation of miR-34a therapeutics into the clinic has been hindered by several issues including delivery vehicle-associated toxicity, inefficient cellular uptake and serum stability, and limited specificity to targeted tumors. The stability problem is due to the sensitivity of unmodified miR-34a oligos to nuclease-mediated degradation, thereby requiring repetitive cycles of high-dose to achieve the desired therapeutic response [ 66 ]. Thus, chemical modifications have been pursued to overcome the issue ( Figure 1 , right).…”
Section: Mir-34a Therapeutic Development For Aggressive Pcamentioning
confidence: 99%
“…The pathway of EVs internalization determines the functional response and efficiency of cargo delivery, while the internalization of EVs is mediated by a variety of mechanisms ( 80 ), including grid protein dependence and endocytosis of grid protein non-dependent pathways ( 78 ). In general, endocytosis is usually divided into two main subgroups: phagocytosis and cytokinesis.…”
Section: Introduction Of Evsmentioning
confidence: 99%
“…Non-dependent endocytosis of grid proteins, including the formation of inverted influxes of vesicle-coated cells on cell membranes ( 77 , 84 , 85 ). Alternatively, fusing with the exoplasmic membrane, EVs can enter cell directly, thereby release their contents into the cytoplasm ( 80 ).…”
Section: Introduction Of Evsmentioning
confidence: 99%